Biological porous carbon encapsulated polyethylene glycol-based phase change composites for integrated electromagnetic interference shielding and thermal management capabilities. (20th June 2022) - Liu, Shuang; Sheng, Mengjie; Wu, Hao; Shi, Xuetao; Lu, Xiang; Qu, Jinping
Abstract: The development of functional composites with excellent thermal management capabilities and electromagnetic interference (EMI) shielding has become extremely urgent for keeping up with the continuous improvement of the operating speed and efficiency for electronic equipment. In this study, the biological wood-derived porous carbon (WPC) was determined as the supporting material to encapsulating polyethylene glycol (PEG), and a series of WPC/PEG/Fe3 O4 phase change composites (PCCs) with excellent shape stability, EMI shielding and thermal management capabilities were prepared via a simple vacuum impregnation method. The Fe3 O4 magnetic particles modified PCCs have greatly improved the EMI shielding effectiveness (SE). The EMI SE of WP-4 (7.5 wt.% Fe3 O4 in PEG) can be up to 55.08 dB between 8.2 − 12.4 GHz, however, the WP-0 without Fe3 O4 addition is only 40.08 dB. Meanwhile, the absorption ratio of electromagnetic waves (EMW) has also increased from 75.02% (WP-0) to 85.56% (WP-4), which effectively prevents secondary pollution. In addition, after wrapping a thin layer of polydimethylsiloxane resin (PDMS), the obtained WP-4 can maintain a high heat storage capacity (109.52 J/g) and good water stability. In short, the prepared WPC/PEG/Fe3 O4 PCCs have great potential application value in the thermal management and electromagnetic shielding requirements for electronic devices.